PENGARUH DOSIS BERBAGAI SUMBER PUPUK KALSIUM TERHADAP PERTUMBUHAN AWAL TANAMAN NANAS DI PT. GREAT GIANT PINEAPPLE LAMPUNG - Arin Novitasari; Retno Suntari; Priyo Cahyono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Characteristic of Ultisol in PT. Great Giant Pineapple is very acidic soil and low of macro and micro nutrient content. This condition can be solved by liming so pineapple plant can growth optimally. There are many material of lime with different shape and size. The purpose of this study was to analyze calcium source with the right doses that can increase pH, provide nutrient available and decrease any toxic elements. This study used a completely randomized design with 18 treatments. The treatment included D0, C0, T0 (control), dolomite with 1, 2, 3, 4 and 5 t ha-1 doses (D1, D2, D3, D4, D5), Granular Calcite with doses of 100, 200, 300, 400, and 500 kg ha-1 (C1, C2, C3, C4, C5) and Suspension of Calcite with doses of 75, 100, 125, 150, 175 L ha-1 (T1, T2, T3, T4, T5). The results showed that application of calcium sources had significant effect on soil pH, Al saturation, Fe available, exchangeable-Ca, exchangeable-Mg, CEC, Base Saturation, available-P, total-N, and exchangeable-K in several time of observations. Application of 5 t dolomite ha-1 increased soil pH, and decreased Al saturation and available-Fe, and it also increased Ca and Mg contents. However, application of dolomite had no significant effects on N, available-P and exchangeable-K at several time of observations. The initial growth parameter was not significantly affected by application of dolomite.